Iron dyshomeostasis and ferroptosis in Alzheimer’s disease: Molecular mechanisms of cell death and novel therapeutic drugs and targets for AD - Zhang, Yuan; Wang, Man; Chang, Wenguang (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is a degenerative disease of the central nervous system that is the most common type of senile dementia. Ferroptosis is a new type of iron-dependent programmed cell death identified in recent years that is different from other cell death forms. Ferroptosis is induced by excessive accumulation of lipid peroxides and reactive oxygen species (ROS) in cells. In recent years, it has been found that ferroptosis plays an important role in the pathological process of AD. Iron dyshomeostasis contribute to senile plaques (SP) deposition and neurofibrillary tangles (NFTs). Iron metabolism imbalance in brain and the dysfunction of endogenous antioxidant systems including system Xc- and glutathione peroxidase (GPX) are closely related to the etiopathogenesis of AD. Dysfunction of nuclear receptor coactivator 4 (NCOA4)-mediated ferritinophagy induced ferroptosis can accelerates the pathological process of AD. In addition, NRF2, through regulating the expression of a considerable number of genes related to ferroptosis, including genes related to iron and glutathione metabolism, plays an important role in the development of AD. Here, we review the potential interaction between AD and ferroptosis and the major pathways regulating ferroptosis in AD. We also review the active natural and synthetic compounds such as iron chelators, lipid peroxidation inhibitors and antioxidants available to treat AD by alleviating iron dyshomeostasis and preventing ferroptosis in mice and cell models to provide valuable information for the future treatment and prevention of AD.